2010
DOI: 10.5539/ijbm.v5n7p117
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Marketing and Public Relations in Not for Profit Hospitals in Nigeria

Abstract: This is my Abtract Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Balogun and Ogunnaike (2017) reported that management of health-care organisations did not place much value on marketing strategies in monitoring or shaping consumer behaviour until recently. However, today, health-care marketing has become an important tool for winning customers by hospitals (Gbadeyan, 2010) and has further stimulated the growth of the medical tourism industry. Technology is also being adapted to market medical tourism as the Taiwanese government has done with the Taiwan Medical Travel App (Chang, Chou, Yeh and Tseng, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Balogun and Ogunnaike (2017) reported that management of health-care organisations did not place much value on marketing strategies in monitoring or shaping consumer behaviour until recently. However, today, health-care marketing has become an important tool for winning customers by hospitals (Gbadeyan, 2010) and has further stimulated the growth of the medical tourism industry. Technology is also being adapted to market medical tourism as the Taiwanese government has done with the Taiwan Medical Travel App (Chang, Chou, Yeh and Tseng, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of these two dynamic factors in designing a successful marketing strategy for the Lebanese hospitals. It is easier and less expensive to retain old patients than to find new ones through the marketing process (Gbadeyan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Los pacientes ahora se informan más acerca de sus necesidades y ya no se someten únicamente a las instrucciones de su médico, puesto que adoptan un papel más activo en las decisiones relacionadas con su salud (Del-Pozo-Irribarría;Ferreras-Oleffe, 2011;Freberg;Palenchar;Veil, 2013;Gbadeyan, 2010;Thomas, 2005;Wrenn, 2002). El aumento de documentos sobre esta temática, así como de fuentes de información, ha podido contribuir (Amador-Romero, 2004;Avery et al, 2010;Brodie;Glynn;Van Durme, 2002;Eggener, 1998;Observatorio de la Comunicación Científica, 2008;Viswanath, 2006).…”
Section: Introductionunclassified